Frequency of Cardiovascular Problems in Patients with Benign Prostate Enlargement - Haris Hamid, Israr Ali Khan, Shafqat Huma, Muhammad Nadeem Khan, Muhammad Ibrahim Khan, Muhammad Salman, Yasir Ali, Ishrat Rahman, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Males often suffer from the genitourinary disorder known as benign prostatic hyperplasia (BPH) also known as benign prostate enlargement (BPE). Various studies observed association between cardiac problems and benign prostate enlargement. Objective: To find out frequency of cardiovascular problems in patients with benign prostate enlargement Methodology: The current study was cross sectional carried out at the Urology Department, Fauji Foundation Hospital Peshawar Cantt. The study duration was twelve months from January 2021 to January 2022. All the collection of data was done by using pre-designed Performa. A consultant cardiologist assessed all the enrolled patients for the cardiovascular problems. All the data analysis was done by SPSS version 23. Results: In the current study, the frequency of hypertension was 28 (23.33%) patients. Out of 28 hypertensive patients, cardiovascular problems were observed in 13 (46.43%) patients. Decreased ejection fraction was observed in 4 (30.77%) patients, left ventricular hypertrophy in 3 (23.08%), left ventricular failure in 2 (15.38%), ischemic heart disease in 3 (23.08%) and non- significant ECG change was observed in only 1 (7.69%) patient. Conclusion: Our study concludes that the frequency of hypertension and cardiovascular problems are high in patients with benign prostate enlargement. To avoid unintended cardiovascular events, such individuals should be thoroughly evaluated. Keywords: Cardiovascular problems; Benign prostate enlargement; Morbidity